Estimating Vegetation Density Dynamics, Tree Diversity, and Carbon Stock in the Agroforestry System of the Community Forest in Bogor Regency, Indonesia - Hartoyo, Adisti Permatasari Putri; Karlinasari, Lina; Setiajiati, Fitta; Wijayanto, Arif Kurnia; Rifana, Haikal Zaky; Madani, Hilmi Naufal; Satriawan, Handi; Rahmawati, Rita; Siregar, Ulfah Juniarti (Department of Forestry, Faculty of Agriculture, University of Lampung, 2025)
Mitigation actions to address climate change are essential to prevent future adverse impacts, with woody species in forests playing a pivotal role in carbon storage, as exemplified by the agroforestry systems commonly practiced in community forests of Bogor Regency, which integrate woody species and crops. This study aimed to analyze changes in vegetation density using the Normalized Difference Vegetation Index (NDVI) approach, analyze stand structure and composition, and estimate above-ground carbon stocks in the agroforestry land of community forest in Tenjolaya Sub-District, Bogor Regency. The methods used were spatial analysis with NDVI, vegetation analysis, and carbon stock estimation using allometric and destructive methods. The plot size was 50 m × 50 m, totaling 21 plots. NDVI analysis resulted in low density (0.59–0.67), moderate density (0.67–0.78), and high density (0.78–0.85). This study found 178 plant species across 40 families, with Fabaceae and Myrtaceae being the most dominant. The carbon stock is 27.69 tons carbon/ha. Carbon stock is significantly influenced by tree density, number of species, and basal area values. A well-managed community forest has high ecological, economic, and social potential through the development of agroforestry, which can maintain biodiversity and environmental sustainability while storing carbon stocks. Keywords: above-ground carbon, agroforestry, community forest, normalized difference vegetation index, vegetation density